Mitos Covid-19 di Kalangan Masyarakat Kota Kupang : Survey Cross-Sectional - M. Dinah Charlota Lerik; Yeni Damayanti (Universitas Nusa Cendana, 2020)
Abstract. Public behavior influences the spread of the new Corona virus desease 2019 (COVID-19). Human behavior is influenced by human knowledge. The objective of the research is to asses the knowledge of COVID-19 among the community. This research is an online cross-sectional survey. The questionnaire consisted of 16 myth statements. Sample of this research used convenience sample consists of 130 people. Data processed by percentage. Result: percentage of 6 statements above 50 percent as facts Keywords: Covid-19, myth, fact, human knowledge